2017
DOI: 10.1016/j.biortech.2016.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing anaerobic digestion performance of crude lipid in food waste by enzymatic pretreatment

Abstract: Three lipases were applied to hydrolyze the floatable grease (FG) in the food waste for eliminating FG inhibition and enhancing digestion performance in anaerobic process. Lipase-I, Lipase-II, and Lipase-III obtained from different sources were used. Animal fat (AF) and vegetable oil (VO) are major crude lipids in Chinese food waste, therefore, applied as substrates for anaerobic digestion tests. The results showed that Lipase-I and Lipase-II were capable of obviously releasing long chain fatty acid in AF, VO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 28 publications
2
17
0
2
Order By: Relevance
“…Subsequent to bio-delipidation, these findings were also confirmed by visual inspection of the tubes, which showed less turbid characteristics for the bio-delipidized samples. [7] and [2] also observed similar results, where the application of lipase enzyme in fatty wastewater reduced turbidity. In this study, the comparative analysis for total protein concentration of DAF pre-treated PSW and bio-delipidized samples was necessary because proteins are huge contributors to pollution and are prevalent in PSW [23].…”
Section: B Effect Of Bio-delipidation On Pre-treated Psw Quality Parsupporting
confidence: 56%
See 1 more Smart Citation
“…Subsequent to bio-delipidation, these findings were also confirmed by visual inspection of the tubes, which showed less turbid characteristics for the bio-delipidized samples. [7] and [2] also observed similar results, where the application of lipase enzyme in fatty wastewater reduced turbidity. In this study, the comparative analysis for total protein concentration of DAF pre-treated PSW and bio-delipidized samples was necessary because proteins are huge contributors to pollution and are prevalent in PSW [23].…”
Section: B Effect Of Bio-delipidation On Pre-treated Psw Quality Parsupporting
confidence: 56%
“…Furthermore, clogging of pipe systems due to the building up of FOG leads to process redundancies. In certain instances, solidified lipids are at low temperatures during anaerobic treatment, a phenomenon that has been reported in numerous studies for slaughterhouse wastewater [2,3,4]. Even after successful primary pre-treatment, further lipid removal might be required in a process.…”
Section: Introductionmentioning
confidence: 94%
“…For example, a study that used slaughterhouse waste feed reported that dilution of inhibitory compounds with co-digestion led to improved methane yield compared to mono-digestion reactors (Astals et al, 2014). Other methods for inhibition mitigation include thermal pre-treatment (Ennouri et al, 2016), alkaline pre-treatment (Koyama et al, 2017), and enzyme addition (Meng et al, 2017). A study that evaluated the addition of three lipases to hydrolyze food waste rich in crude lipid revealed that using two of the lipases increased methane production by 81-158% in animal fat, 27-54% in vegetable oil, and 37-41% in floatable grease waste digestions (Meng et al, 2017).…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…A previous study showed that the lag phase of wastes rich in lipids was about 20.2-48.7 d. This was much longer than that of other wastes (about 14.9-19.9 d) (Lou et al, 2012). A study by Meng et al (2015) showed that FW in China (rich in lipids such as floatable grease from animal fat and vegetable oil), could greatly benefit from lipase additive during hydrolysis, with methane production increase of 37.0-40.7% in digestion time of 10-40 d (Meng et al (2017).…”
Section: Specific Role Of Enzymes For Different Fw Componentsmentioning
confidence: 99%